The Influence Of Financial Statement Ratio On Profit Growth (Food And Beverages Companies Listed On The IDX Period 2018 - 2022) - Carolina Ety Widjayanti; Najmudin Najmudin (Cita konsultindo, 2024)
Financial Statements are very important information in economic decision making or corporate activity. But it is necessary to know the financial statements of the company has the nature of limitations, such as historical nature, all financial statements are basically a historical document. The purpose of this research is to know the influence of ratio of financial statements to profit growth (food and beverages companies listed in period 2018 - 2022). The results of this study is Net Profit Margin (NPM), no significant effect and positive effect on profit growth. Current Ratio (CR), does not have a significant and negative effect on profit growth. Debt to Asset Ratio (DAR), no significant effect and negatively affect the profit growth. Return On Asset Ratio (ROA), no significant effect and positive effect on profit growth.